Anomalous Electronic and Protonic Conductivity of 2D Titanium Oxide and Low‐Temperature Power Generation Using Its Protonic Conduction. Issue 20 (26th September 2021) - Lee, Sang Eun; Jung, Sung Yeb; Seo, Jun; Joo, Jong Hoon; Lee, Jaekwang; Kim, Young‐Min; Lee, Kyu Hyoung; Kim, Yong In; Park, Hee Jung
Abstract: In this study, a titanium‐oxide film is fabricated by stacking 2D nanosheets with a thickness of 1 nm layer‐by‐layer. The electrical properties of the titanium‐oxide film are investigated under various temperatures (25–300 °C) and a water vapor atmosphere. As a result, it is found that protonic conduction is dominant at low temperatures (<100 °C), while electronic conduction is highest at high temperatures (>200 °C). The electrical conductivity is about one billion times higher than that of conventional 3D titanium‐oxide. Protons, dominant charge carriers at low temperature, are transported along the pathway between layers of nanosheets. The protonic conductivity is as high as 10 −4−5 S cm −1 due to the increased interfacial density of the film. This anomalous electronic and protonic conduction is expected to be available in various applications. In this study, the developed 2D titanium‐oxide with high protonic conductivity is employed in the solid electrolyte of a solid oxide fuel cell using water as a fuel. A competitive power density of ≈0.22 mW cm −2 is obtained at low temperature (75 °C) under a water concentration gradient. Abstract : The film manufactured by laminating titanium‐oxide nanosheets with 1 nm thickness maximizes the interfacial density of the film and leads to enhanced protonic conductivity at low temperature. Its electronic conduction estimated in high temperature regions is colossal. The nanosheet film is employed in a solid oxide fuel cell operated with water fuel at low temperature.